2005
DOI: 10.1085/jgp.200509334
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Regarding the Operational Characteristics and Teleological Purpose of the Renal Na+-K+-Cl2 Cotransporter (NKCC2s) Splice Variants

Abstract: The absorptive Na+-K+-Cl− cotransporter (NKCC2) is a polytopic protein that forms homooligomeric complexes in the apical membrane of the thick ascending loop of Henle (TAL). It occurs in at least four splice variants (called B, A, F, and AF) that are identical to one another except for a short region in the membrane-associated domain. Although each of these variants exhibits unique functional properties and distributions along the TAL, their teleological purpose and structural organization remain poorly define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
2
45
1
Order By: Relevance
“…Similar results were recently obtained for rats. Again, water loading led to decreased expression levels of the NKCC2 A and F isoform (1). In contrast to NKCC2 mRNA expression, vasopressin has been shown to increase NKCC2 protein abundance and the protein phosphorylation status, resulting in augmented membrane trafficking (2,6,9,18,31).…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were recently obtained for rats. Again, water loading led to decreased expression levels of the NKCC2 A and F isoform (1). In contrast to NKCC2 mRNA expression, vasopressin has been shown to increase NKCC2 protein abundance and the protein phosphorylation status, resulting in augmented membrane trafficking (2,6,9,18,31).…”
Section: Discussionmentioning
confidence: 98%
“…Given that each of the CCCs exhibits unique functional properties and that several of these carriers coexist in various cell types, it would be of interest to determine whether the four K ؉ -Cl ؊ cotransporter (KCC) isoforms and their splice variants can also assemble into such units and, more importantly, whether they can form heterooligomers by interacting with each other or with the secretory Na (1-3), and the KCCs exist as four isoforms and several splice variants (at least five for KCC3 and two for KCC1) (4 -11). All of these structures are predicted to contain 12 transmembrane domains flanked by cytoplasmic termini (1,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The NKCCs exist as two isoforms (1)(2)(3), and the KCCs exist as four isoforms and several splice variants (at least five for KCC3 and two for KCC1) (4 -11). All of these structures are predicted to contain 12 transmembrane domains flanked by cytoplasmic termini (1,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Because the junction point of this chimera was similar to the one that was used for KCC2 4-2-2 , residues proximal to amino acid 644 could thus play a structural role as well (2). We have recently found that the proximal and distal Ct of the NKCCs, which are closely related to the KCC isoforms, are capable of self-interactions (43,49), suggesting that residues between these distant protein segments can associate with one another in the context of intramolecular and intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolocalization of KCCs Expressed in X. laevis Oocytes-These studies were performed as described in previous publications by our group (41)(42)(43)(44). Briefly, oocytes cryosections (10 m) were postfixed for 30 min in paraformaldehyde and incubated sequentially with a primary and secondary antibody (for 1 h each at room temperature).…”
Section: B) Kcc4mentioning
confidence: 99%